Quantitative airway assessment on computed tomography in patients with α(1)-antitrypsin deficiency - Yamashiro, Tsuneo (2009)
BACKGROUND: The relationship between quantitative airway measurements on computed tomography (CT) and airflow limitation in individuals with severe α(1)-antitrypsin deficiency (AATD) is undefined. OBJECTIVES: To clarify the relationship between CT-based airway indices and airflow limitation in AATD. METHODS: 52 patients with AATD underwent chest CT and pre-bronchodilator spirometry at three institutions. In the right upper (RUL) and lower (RLL) lobes, wall area percent (WA%) and luminal area (Ai) were measured in the third, fourth, and fifth generations of the bronchi. The severity of emphysema was also calculated in each lobe and expressed as low attenuation area percent (LAA%). Correlations between obtained measurements and FEV(1)% predicted (FEV(1)%P) were evaluated by the Spearman rank correlation test. RESULTS: In RUL, WA% of all generations was significantly correlated with FEV(1)%P (3(rd),R=−0.33, p=0.02; 4(th),R=−0.39, p=0.004; 5(th),R=−0.57, p<0.001; respectively). Ai also showed significant correlations (3(rd),R=0.32, p=0.02; 4(th),R=0.34, p=0.01; 5(th),R=0.56, p<0.001; respectively). Measured correlation coefficients improved when the airway progressed distally from the third to fifth generations. LAA% also correlated with FEV(1)%P (R=−0.51, p<0.001). In RLL, WA% showed weak correlations with FEV(1)%P in all generations (3(rd),R=−0.34, p=0.01; 4(th),R=−0.30, p=0.03; 5(th),R=−0.31, p=0.03; respectively). Only Ai from the fifth generation significantly correlated with FEV(1)%P in this lobe (R=0.34, p=0.01). LAA% strongly correlated with FEV(1)%P (R=−0.71, p<0.001). CONCLUSIONS: Quantitative airway measurements are significantly correlated with airflow limitation in AATD, particularly in the distal airways of RUL. Emphysema of the lower lung is the predominant component; however, airway disease also has a significant impact on airflow limitation in AATD.